2016
DOI: 10.1016/j.ajog.2016.01.163
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamics of transdermal granisetron in women with nausea and vomiting of pregnancy

Abstract: Granisetron significantly improved symptoms of nausea and vomiting as gauged by the PUQE score. After IV infusion the reduction in PUQE score was observed within 1 day. When granisetron was administered as a patch, benefit likewise was seen within 1 day suggesting rapid absorption of the medication transdermally. The beneficial effect of transdermal granisetron on the PUQE score persisted for the entire 7 days during which the patch was in place. In this small cohort, the granisetron patch appeared to be effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 13 publications
0
9
1
Order By: Relevance
“…For these patients the transdermal route as a simple method to deliver drug has a significant added value and can improve patient’s compliance (Zur, 2013). In this context our group has recently evaluated the pharmacodynamics of granisetron (category B), administered with a transdermal patch to women with NVP (Caritis et al, 2016). The study demonstrated that granisetron significantly improved symptoms of NVP.…”
Section: Treatmentmentioning
confidence: 99%
“…For these patients the transdermal route as a simple method to deliver drug has a significant added value and can improve patient’s compliance (Zur, 2013). In this context our group has recently evaluated the pharmacodynamics of granisetron (category B), administered with a transdermal patch to women with NVP (Caritis et al, 2016). The study demonstrated that granisetron significantly improved symptoms of NVP.…”
Section: Treatmentmentioning
confidence: 99%
“…To our knowledge, this is the first study to demonstrate that polymorphisms in CYP3A5 and CYP1A1 can affect the AUC and clearance of granisetron. Our findings may account for the observed variability in granisetron exposure and thereby antiemetic efficacy in women treated for NVP …”
Section: Discussionmentioning
confidence: 66%
“…The methods and primary results of this study have been reported previously . In brief, we conducted a pharmacokinetic study of granisetron in 16 pregnant women from gestational ages 12–19 weeks with NVP.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, GTDS has been successfully used in women with nausea and vomiting associated with pregnancy who could not tolerate administration via the oral route. The reduction of nausea and vomiting was observed within one day, suggesting that the onset of action with the transdermal delivery was comparable with the intravenous infusion [41]. In chronic pain management, opioid titration is a critical step in patient compliance; unfortunately, even though tolerance reduces the incidence of opioid-induced nausea and vomiting over time, its incidence can be high and impair patients' impression of the received treatment, leading to withdrawal for adverse events.…”
Section: Discussionmentioning
confidence: 92%